Analisis Faktor Determinan Kejadian Hidronefrosis Di RSUD Dr.M.M Dunda Limboto Kabupaten Gorontalo - Dakio, Ferawati; Kadir, Sunarto; Kasim, Vivien N. A (Health Information : Jurnal Penelitian, 2023)
Hydronephrosis is one of the urological problems that are often encountered in clinical practice. This condition is characterized by fluid buildup in the kidneys due to obstruction of urine flow. The purpose of this study was to analyze the determinants of hydronephrosis events in patients at Dr.M.M Dunda Limboto Hospital. Type of analytical observational research with a cross sectional study approach. The samples in this study were patients who were carried out abdominal ultrasound at the Radiology Installation when the study took place a total of 85 samples. Based on the results of the study, it can be concluded that the age of p-value = 0.006 (<0.05), blood pressure p-value = 0.027 (<0.05), kidney stones p-value = 0.000 (<0.05) has a significant relationship with the incidence of hydronephrosis with kidney stones being the variebal most associated with the incidence of hydronephrosis.